Analisis Pengaruh Intellectual Capital Dan Working Capital Terhadap Profitabilitas Bank Umum Syariah BUMN - Siti Nur Rosida; Esy Nur Aisyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
State-owned sharia commercial banks are the highest assets of Islamic banking in Indonesia. As a financial institution operating in a country that operates a dual banking system, it is required to compete with conventional banking. Facing fairly fierce competition, Islamic banking is required to manage all its capital to generate profitability. Both non-physical capital, intellectual capital (intellectual capital), knowledge, and physical capital to operate the company, namely working capital. The purpose of this study was to see the effect of intellectual capital and working capital on the projected profitability of Return on Assets (ROA). The research used descriptive statistical method with analysis tools in panel data regression which was processed using Eviews 10 software. Techniques and data used the method of documentation and literature study and sampling with the purposive sampling method so that the number of samples in this study was 72 samples of State-owned Sharia Commercial Banks with quarterly data for the 2015-2020 period. The results obtained indicate that simultaneously the independent variables, namely Intellectual Capital (X1) and Working Capital (X2), have a significant effect on Return On Assets (ROA). The second independent variable can explain the dependent variable by 54.2%, and the remaining 45.8% is another variable that is not included in the model. The study results partially show that Intellectual Capital (X1) has a positive and significant effect on Return On Assets (ROA). However, the Working Capital variable (X2) does not affect the Return on Assets (ROA) of BUMN Commercial Sharia Banks in 2015-2020.